Characterization of ESBL-Producing Escherichia coli and Klebsiella pneumoniae Isolated from Clinical Samples in a Northern Portuguese Hospital: Predominance of CTX-M-15 and High Genetic Diversity - Isabel Carvalho; José António Carvalho; Sandra Martínez-Álvarez; Madjid Sadi; Rosa Capita; Carlos Alonso-Calleja; Fazle Rabbi; Maria de Lurdes Nunes Enes Dapkevicius; Gilberto Igrejas; Carmen Torres; Patrícia Poeta (Microorganisms, 2021)
Background: Enterobacteriaceae are major players in the spread of resistance to β-lactam antibiotics through the action of CTX-M β-lactamases. We aimed to analyze the diversity and genetic characteristics of ESBL-producing Escherichia coli and Klebsiella pneumoniae isolates from patients in a Northern Portuguese hospital. Methods: A total of 62 cefotaxime/ceftazidime-resistant E. coli (n = 38) and K. pneumoniae (n = 24) clinical isolates were studied. Identification was performed by MALDI-TOF MS. Antimicrobial susceptibility testing against 13 antibiotics was performed. Detection of ESBL-encoding genes and other resistance genes, phylogenetic grouping, and molecular typing (for selected isolates) was carried out by PCR/sequencing. Results: ESBL activity was detected in all 62 E. coli and K. pneumoniae isolates. Most of the ESBL-producing E. coli isolates carried a blaCTX-M gene (37/38 isolates), being blaCTX-M-15 predominant (n = 32), although blaCTX-M-27 (n = 1) and blaCTX-M-1 (n = 1) were also detected. Two E. coli isolates carried the blaKPC2/3 gene. The lineages ST131-B2 and ST410-A were detected among the ESBL-producing blood E. coli isolates. Regarding the 24 ESBL-producing K. pneumoniae isolates, 18 carried a blaCTX-M gene (blaCTX-M-15, 16 isolates; blaCTX-M-55, 2 isolates). All K. pneumoniae isolates carried blaSHV genes, including ESBL-variants (blaSHV-12 and blaSHV-27, 14 isolates) or non-ESBL-variants (blaSHV-11 and blaSHV-28, 10 isolates); ten K. pneumoniae isolates also carried the blaKPC2/3 gene and showed imipenem-resistance. ESBL-positive E. coli isolates were ascribed to the B2 phylogenetic group (82%), mostly associated with ST131 lineage and, at a lower rate, to ST410/A. Regarding K. pneumoniae, the three international lineages ST15, ST147, and ST280 were detected among selected isolates. Conclusions: Different ESBL variants of CTX-M (especially CTX-M-15) and SHV-type (specially SHV-12) were detected among CTX/CAZRE. coli and K. pneumoniae isolates, in occasions associated with carbapenemase genes (blaKPC2/3 gene).